Māḍakholakara, vāṅmaya āṇi vyaktimatva - Deśapāṇḍe, Mādhava Kā. (Mādhava Kāśinātha) (SAMP early 20th-century Indian books project, 1948)
Study on the works of Gajanan Tryambak Madkholkar, 1899-1976, Marathi author.